Sellar Colloid Cyst—An Anatomically Aberrant and Diagnostically Challenging Entity: Report of a Rare Case with Literature Review - Ali, Syed Asmat; Gaur, Kavita; Srivastava, Arvind Kumar; Saran, Ravindra Kumar (Indian Journal of Neurosurgery, 2019)
The sellar colloid cyst is a rare entity anatomically occurring at the intermediate lobe of the pituitary gland. Clinically a cystic sellar lesion with pressure effects usually evokes the suspicion of a pituitary adenoma. We present the case of a middle-aged woman presenting with visual diminution and bilateral optic atrophy, caused by a large sellar lesion, variably intense on magnetic resonance imaging (MRI). The subsequent histologic diagnosis of a colloid cyst was unexpected. This report highlights the subtle intraoperative and diagnostic features key to diagnosing this rarity. We also discuss a practical differential diagnostic approach relevant to the practicing surgeon and review the existing literature.
Keywords: colloid cyst; pituitary; magnetic resonance imaging